Selection of the models and criteria for analysis and evaluation of nursing theory - Pajnkihar, Majda; Donik, Donik; Čuček Trifković, Klavdija; Kegl, Kegl; Prlić, Nada; Radić, Rade; Stričević, Jadranka (Nursing in the 21st Century, 2012)
SELECTION OF THE MODELS AND CRITERIA FOR ANALYSIS AND EVALUATION OF NURSING THEORYAim. Nursing theories always underline and describe the concepts, which are in the interest of nursing and the patients in a certain period of time and space. Analysis and evaluation of nursing theories represent an evaluation of a theory according to its usefulness in practice, education and research. Theory evaluation is a process in which a theory is systematically reviewed.Material and Methodology. The research was supported by quantitative methodology with two structured questionnaires. Evaluation was based upon the use of Likert's scale from 1 (the worst) to 4 (the best). The students have described the model evaluation also in qualitative terms. A sample of graduate students at the University Slovenia, (1) Slovenia (n= 24) and at the University in Croatia (2), Croatia (n=38), both in the first year of the second Bologna degree in nursing was consciously designed.Results. The results demonstrate that students from both Universities have singled out clarity with mean grade of 3.9, utility with mean grade of 3.8, and simplicity with mean grade 3.8, as the most important criteria for theory analysis and evaluation. Concerning the evaluation of nursing theory analysis and evaluation models of different authors the students have selected McKenna's model (1997), graded with the mean grade of 3.8, as the most useful one according to the required criteria of simplicity, complexity and utility.Discussion. Analysis and evaluation of a selected theory is performed according to a set of evaluation criteria, therefore also the latter need to be presented in a clear and simple manner. It is important that the contents do not repeat themselves and that they lead the user through the process. If possible it is also valuable if the criteria are presented in the form of diagram.Conclusions. The heart and soul of development, analysis and evaluation of a theory lie in the knowledge and education of nurses.